When Will Human Capital in Indonesia be Equal? A Convergence Analysis - Nayaka Artha Wicesa; Axellina Muara Setyanti (The Journal of Indonesia Sustainable Development Planning, 2021)
One of the problems faced by developing countries is income inequality, which is caused by weak and uneven human capital between regions. This research aims to determine the convergence of human capital in absolute and conditional with the explanatory variable of government expenditure in education. The method used is panel data regression with generalized least square and robust standard error. The results showed that provinces in Indonesia experienced human capital convergence in absolute, where inequality of human capital among provinces tended to decline over time and towards equity. The results also showed that provinces in Indonesia experienced human capital convergence in conditional, where government expenditure in education was able to accelerate the convergence process, but not significantly. This study also found that the time needed to equalize human capital in Indonesia is 164 years.